1992
DOI: 10.1007/bf02347091
|View full text |Cite
|
Sign up to set email alerts
|

Germination ecology of coastal plants in relation to salt environment

Abstract: Responses of seed germination to salinity were examined using 37 species collected from salt marshes, cliffs, and fore (unstable) and hind (stable) sand dunes along Japanese coasts. For comparison, seed germination of nine inland species was also examined. The soil salinities in salt marshes ranged from 150 to 300 mmol/L NaC1, whereas those in fore and hind dunes ranged from 0 to 50 mmol/L NaC1, with a few exceptions. Cliff soils showed relatively high salinities up to 300 mmol/L NaCI. Cliff and foredune soils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Because the early stages of plant growth are sensitive to habitat salinity (Baldwin et al, 1996;Mariko et al, Table 4. Effect of salinity (NaCl) concentration in the nutrient solution, on leaf area (LA), specific leaf area (SLA), density of the leaf tissue (D), relative water content (RWC), succulence (S), water content at saturation (WCS) and water saturation deficit (WSD) of Melilotus indicus (n ¼ 5).…”
Section: Greenhouse Experiments Germination and Growthmentioning
confidence: 99%
“…Because the early stages of plant growth are sensitive to habitat salinity (Baldwin et al, 1996;Mariko et al, Table 4. Effect of salinity (NaCl) concentration in the nutrient solution, on leaf area (LA), specific leaf area (SLA), density of the leaf tissue (D), relative water content (RWC), succulence (S), water content at saturation (WCS) and water saturation deficit (WSD) of Melilotus indicus (n ¼ 5).…”
Section: Greenhouse Experiments Germination and Growthmentioning
confidence: 99%
“…One previous study of C. soldanella showed that, although pretreatment with sulfuric acid increased germination to 90% (Mariko et al, 1992), the treatment period was too long and the length of the evaluation was not definite. In contrast, our current research demonstrated that a 3-h pretreatment of stirring with H2SO4 resulted in 100% success, a rate that was significantly higher than any of our other pretreatments.…”
Section: Discussionmentioning
confidence: 96%
“…Cliffs have an irregular salt regime depending on winds, waves and rain. Mariko et al (1992) suggested that plants colonizing sea cliffs need a larger tolerance to salinity in the growing season than in the germination period. Fern spores could germinate at relatively high salt conditions, but if substrate salt concentration of their growing place would not be sufficiently diluted gametophyte development would be hampered or at least reduced and retarded so that gametangia production might fail.…”
Section: Article In Pressmentioning
confidence: 98%
“…Such a pattern would exclude A. marinum from places where salinity is constant. But salinity is more variable in cliffs than in other saline environments (Mariko et al, 1992). Salt marshes, influenced by the tide regime, have a uniform salt contribution, although periodical.…”
Section: Article In Pressmentioning
confidence: 99%